Bayani, Irfani and Burhani Epistemology as the Basic of Science Development in Islam - Ahmad Muzammil; Syamsuri Syamsuri; Achmad Hasan Alfarisi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Epistemology or the theory of science is a very crucial study, because it discusses a very fundamental aspect of human life, namely science. Epistemology investigates philosophically about the structure, methods, validity and goals of science. In the development of Islamic philosophy, epistemology as a new discipline of science that examines intuition and revelation. Intuition is knowledge that comes from God in the form of new views without deduction, speculation and observation. This kind of knowledge in Islam is called Ilm al-Wahby or 'Ilm al-Laduny whose position is lower than revelation. There are three epistemologies of science in Islam, namely bayani, irfani and burhani epistemologies. Bayani epistemology departs from religious texts using an orthodox approach, Burhani epistemology uses a philosophical approach, while Irfani epistemology uses a mystical approach. The approach used in this study is a qualitative research approach. This type of research is Library Research, which is an attempt to obtain data from various books or references